2014
DOI: 10.1007/s10811-014-0406-3
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly of transcriptome from the gametophyte of the marine red algae Pyropia seriata and identification of abiotic stress response genes

Abstract: Pyropia seriata, a marine red alga belonging to the order Bangiales (Rhodophyta), is one of the most valuable and widely cultivated Pyropia species. Water temperature and salinity are major factors affecting the growth and yield of Pyropia cultivation. Currently, there is limited data regarding the regulatory pathways and molecular mechanisms of the abiotic stress responses in red algae. In this study, we generated 1,403,321 expression sequence tags (ESTs) using 454 sequencing technology from the gametophyte t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 44 publications
(53 reference statements)
1
9
0
1
Order By: Relevance
“…Growth bottles containing P. tenera were transferred to a 20°C growth chamber with the same light intensity and photoperiod for the heat treatment. Desiccation and freezing stress were applied as described by Im et al (2015).…”
Section: Plant Materials and Growth Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth bottles containing P. tenera were transferred to a 20°C growth chamber with the same light intensity and photoperiod for the heat treatment. Desiccation and freezing stress were applied as described by Im et al (2015).…”
Section: Plant Materials and Growth Conditionmentioning
confidence: 99%
“…Pyropia grow naturally in the intertidal zone, where they are frequently exposed to a variety of potentially stressful environmental including variations in humidity, changes in temperature, osmotic shock and different light intensities (Hwang et al 1997;Blouin et al 2011). Therefore, Pyopia have developed a variety of strategies and mechanisms to respond to and survive through those environmental stresses (Choi et al 2013;Im et al 2015). Pyropia exhibits a exhibits a heteromorphic life cycle with an alternation of generation between foliose thallus gametophyte and filamentous sporophyte; this is referred to as conchocelis phase (Sahoo et al 2002, Blouin et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Because an increase in temperature affects the growth and productivity of maricultured seaweeds, much effort has been invested to establish and analyze heat stress-tolerant strains of Bangiales (Yan et al 2010, Ding et al 2016, Wang et al 2018a, Lee et al 2019). In addition, transcriptome analyses have generated information concerning heat-inducible andrepressible genes (Choi et al 2013, Im et al 2015, Sun et al 2015, Cao et al 2017, Wang et al 2018a, which has indicated that Bangiales can respond to heat stress. However, knowledge concerning the regulatory mechanisms underlying the heatstress response, tolerance, and memory in Bangiales and other seaweeds is lacking.…”
mentioning
confidence: 99%
“…Draft genome of Pyropia yezoensis has been released (Niu et al 2011;Nakamura et al 2013), and transcriptome of Pyropia and Porphyra has been compared for life stages and under stress (Chan et al 2012;Choi et al 2013;Xie et al 2013;Im et al 2015).…”
Section: Introductionmentioning
confidence: 99%